Pendaftaran Kompetisi Antar Sekolah pada SMA Don Bosco 1 Berbasis Web - Stevan Iskandar; Ziveria , Mira (KALBISCIENTIA Jurnal Sains dan Teknologi, 2024)
Don Bosco 1 senior high school Kelapa Gading is a school that still uses conventional cup registration system in processing participants data, so it takes a long time to process it. This study aims to build a web-based cup registration information system that includes the processing of cup data and cup registration with prototype system development methods that included system anaylysis using cross functional diagram, system design using Unified Modeling Language (UML), system development and programming using Hypertext Preprocessor (PHP) programming language and My Structure Query Language (MySQL) database and system testing using black box with alpha testing. The result of this study is a system that can be used to manage committee data, cup data and cup registration data.